MiR-106b-responsive gene landscape identifies regulation of Kruppel-like factor family. Issue 3 (4th March 2018) - Wehrkamp, Cody J.; Natarajan, Sathish Kumar; Mohr, Ashley M.; Phillippi, Mary Anne; Mott, Justin L.
ABSTRACT: MicroRNA dysregulation is a common feature of cancer and due to the promiscuity of microRNA binding this can result in a wide array of genes whose expression is altered. miR-106b is an oncomiR overexpressed in cholangiocarcinoma and its upregulation in this and other cancers often leads to repression of anti-tumorigenic targets. The goal of this study was to identify the miR-106b-regulated gene landscape in cholangiocarcinoma cells using a genome-wide, unbiased mRNA analysis. Through RNA-Seq we found 112 mRNAs significantly repressed by miR-106b. The majority of these genes contain the specific miR-106b seed-binding site. We have validated 11 genes from this set at the mRNA level and demonstrated regulation by miR-106b of 7 proteins. Combined analysis of our miR-106b-regulated mRNA data set plus published reports indicate that miR-106b binding is anchored by G:C pairing in and near the seed. Novel targets Kruppel-like factor 2 (KLF2) and KLF6 were verified both at the mRNA and at the protein level. Further investigation showed regulation of four other KLF family members by miR-106b. We have discovered coordinated repression of multiple members of the KLF family by miR-106b that may play a role in cholangiocarcinoma tumor biology.